PELATIHAN MENGKEMAS PAKET AGROWISATA BAGI ANGGOTA KELOMPOK TANI DI DESA KERTA, KECAMATAN PAYANGAN, KABUPATEN GIANYAR - SUDANA, IP; MAHADEWI, NP EKA (Buletin Udayana Mengabdi, 2015)
The development of agro-tourism potential in the village of Kerta are appropriately done by introducing them to travelers. This was done in order that farming communities receive economic benefits, such as the availability of additional jobs and to increase sales of agricultural products, especially in the form of citrus and floral crops. Efforts that can be taken is a manufacture of innovative agro-tourism packages in order to attract the number of tourists visiting the village of Kerta and improving the quality of human resources. In order to develop further Kerta village, devoteed Team has successfully trained farmer groups in making tour package entitled ”Bali Organic Farming Activities” meaning that tourist activity to recognize various types of plants. Apart from this, the farmers obtained benefits and watch the activity of farmers and directly involved in managing land in plantation farmer groups Sekar Bumi and farmer groups Teak Bloom. The agro-tourism activities that take tourists to cultivate and reap immediate agricultural products to be processed into the local cuisine of Bali (Balinese Cooking Experience). The second package is already manifested in the form of brochures. Keywords: agro-tourism, tour package and Bali Organic Farming Activities